Management Analysis in Improving the Quality of Educational Institutions at the Central of Jagaan Bestari Impian Bukit Mertajam Malaysia - Prastyo, Windu Fani; Amsari, Syahrul (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
This study aims to determine management in improving institutional quality at the Central of Jagaan Bestari Impian Bukit Mertajam. The research method used is qualitative, with a type of field approach. Data collection techniques were used, namely interviews, observation, and documentation. Data analysis in this study used the interactive model of Miles & Huberman, with research starting from data collection, data reduction, data presentation, verification, and narration of conclusions. Data validity techniques use extended observations and reference materials. The high quality of teachers and staff, efficient management, cooperation with parents/guardians and the community, and attention to children's health and safety are the main factors that support the development of children in this care center. With continuous monitoring and evaluation, the center can continue to improve its services and have a greater positive impact on children and the community